Implementasi Business Intelligence Guna Meningkatkan Loyalitas Dan Kepuasan Pelanggan Pada Aplikasi Ojek Online - Renaldo Wildan firmansyah; Jeni Susyanti; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The phenomenon of online ojek is already endemic in Indonesia. The presence of mobile applications that sell online transportation services, changes the way people order transportation modes easily and quickly, simply by using a smartphone device. Business intelligence at the online ojek company itself, namely implementing the big data concept, this is done because online ojek always get a lot of historical data, it is necessary to know that this must be read quickly and carefully. This study aims to determine the effect of implementing business intelligence on online ojek applications to increase customer loyalty and customer satisfaction. This study uses a non-probability sampling method with a purposive sampling technique. Determination of the number of samples using the Slovin formula which obtained 91 respondents. The respondents are university students and students at the Faculty of Economics and Business, the Islamic University of Malang who use an online ojek application. Simple linear regression analysis was used to evaluate the causal model through SPSS 26. The results of this study found that business intelligence had a significant and positive effect on increasing customer loyalty and customer satisfaction. Keywords: Business Intelligence, Customer Loyalty, Customer Satisfaction.